Los Assamiidae (Opiliones: Assamiidae) de Río Muni (Guinea Ecuatorial), con la descripción de ocho nuevas especies - Santos, Rakel (2010)
The Opiliones from Equatorial Guinea’s Continental Region (formerly Río Muni) had not been studied previously. A collection made in 1996 produced 22 species, ten of which belong to the Assamiidae and are studied herein: Chilon robustus and Mbinia xenophora gen. nov., sp. nov. (Erecinae); Podauchenius longipes and Rhabdopygus funilignorum sp. nov. (Hypoxestinae); Ayenea trimaculata gen. nov., sp. nov., Montalenia forficula gen. nov., sp. nov. and Niefanga spinosa gen. nov., sp. nov. (Polycoryphinae); Binderia longipes sp. nov., Seuthes inermis sp. nov. and Seuthessus coriscanus sp. nov. (Selencinae). We con-sider Ayenea, Montalenia and Niefanga an informal suprageneric group characterized by two orifices on the dorsal side of the penis and a thick genital operculum. Identification keys to species of these taxa are provided, together with color photographs of both sexes (except the female of Binderia longipes). Eight of the ten assamiid species have been recorded from the Monte Alén National Park; only two selencine species (apparently coastal) are absent.